Nigeria zero hunger/IITA Policy brief No. 1: Nigeria zero hunger strategic review - nutritional status of children under the age of 5 in Benue state, Nigeria - Okike, Iheanacho; Ayoola, G.B.; Ogundapo, A.T.; Ojide, M.; Abdoulaye, Tahirou; Dashiell, Kenton E.; Manyong, Victor (Herald Scholarly Open Access, 2021)
In the Global Nutrition Report (GNR) of 2015, Nigeria was grouped along with other countries where only a minority of children are growing healthily [1].